Edge-on orientation of thermally evaporated metal phthalocyanines thin films for humidity sensing application - Natashah, Fadlan Arif; Hisamuddin, Syaza Nafisah; Coffey, Aidan H.; Zhu, Chenhui; Bawazeer, Tahani M.; Alsoufi, Mohammad S.; Roslan, Nur Adilah; Supangat, Azzuliani (Springer, 2024)
Thermally evaporated metal phthalocyanines (MPcs) were successfully fabricated for humidity-sensing applications. Comparative molecular analysis of three different MPcs sensing layers, namely MnPc, VOPc, and VTTBNc, using the powerful tool of grazing-incidence wide-angle and small-angle X-ray scattering (GIWAXS/GISAXS), were made to find the correlation between molecule orientation of the sensing layers and their humidity sensing performances. In this study, planar-configurated capacitive Al/MnPc/Al humidity sensor produced the highest sensitivity (17.74 nF/%RH) relative to Al/VTTBNc/Al (11.50 nF/%RH) and Al/VOPc/Al (11.20 nF/%RH) due to its crystallographic orientation being more vertical than the VTTBNc and VOPc counterparts, as confirmed by GIWAXS and GISAXS analysis. Similarly, the MnPc-based sensor produced the fastest response and recovery time of 3 s and 2 s, respectively. Meanwhile, VTTBNc yielded the smallest hysteresis gap of 0.29%. The quantitative and qualitative information, such as crystal coherence length, grain size, and lattice spacing obtained from the GIWAXS and GISAXS, have been studied to explain the humidity sensors’ sensitivity, hysteresis, and transient response. The crystallographic orientation of the active sensing layer significantly influences the humidity sensing performance.